Does Self-Efficacy of Teachers Toward Inclusive Education Differ Between Primary and Secondary School? A Cross-Cultural Study of Ghana and the United Arab Emirates - Mohamed, A; Opoku, MP; Guirguis, BM; Gyimah, EM; Al Yafi, M; Alqahtani, S; Alharthi, S; Aldhanhani, M; Aljaberi, AZ (Elsevier BV, 2026)
There are ongoing debates on the level of education that students with special educational needs could participate in and enjoy as part of their fundamental right to education. There is a notion that students with special educational needs could be more easily included in primary schools than in secondary schools. However, teachers were excluded from such discussions. The current study aims to invigorate such discussion by exploring primary and secondary school teachers' self-efficacy across Ghana and the United Arab Emirates (UAE). a total of 897 teachers were recruited from Ghana and the UAE to rate their self-efficacy via the Teacher Efficacy for Inclusive Practice Scale. The study findings provide theoretical support for the Teacher Efficacy for Inclusive Practice Scale as an appropriate instrument for examining teachers’ self-efficacy in Ghana and the UAE. The findings also revealed differences between teachers in terms of gender, participation in professional development, level of teacher and school type. The study concludes with a recommendation for national dialogue to develop the scope of teacher self-efficacy across both Ghana and UAE. Other study implications are discussed.
Keywords: 3901 Curriculum and Pedagogy; 3903 Education Systems; 3904 Specialist Studies In Education; 39 Education; 4 Quality Education